2018
DOI: 10.1177/0272431618812157
|View full text |Cite
|
Sign up to set email alerts
|

Parental Supervision, Executive Functions, and Emotional-Behavioral Problems in Chinese Immigrant and Italian Nonimmigrant Early Adolescents in Italy

Abstract: The current study aimed to examine whether executive functioning (EF) moderates the expected association between poor parental supervision and emotional-behavioral problems among early adolescents with and without a migration background in Italy. In total, 97 Chinese immigrant and 165 Italian nonimmigrant early adolescents, aged 11 to 13 years (52% girls), completed a series of performance and computer-based tasks assessing their EFs, whereas primary caregivers rated their own parental supervision and their of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Content may be shared at no cost, but any requests to reuse this content in part or whole must go through the American Psychological Association. context of migration (Miconi et al, 2019a), possibly contributing to early adolescents' implicit definition of their own self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…Content may be shared at no cost, but any requests to reuse this content in part or whole must go through the American Psychological Association. context of migration (Miconi et al, 2019a), possibly contributing to early adolescents' implicit definition of their own self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a study of Mexican-origin adolescents in the United States, Park, Wang, Williams, and Alegría (2018) reported that the link between racial discrimination and adjustment (assessed as externalizing and internalizing problems) was attenuated for youth with higher as opposed to lower levels of anger suppression, whereas elevated anger expression exacerbated this link. In the European context, a recent study highlighted the protective role of behaviorally measured impulse control in the association between perceived discrimination and externalizing problems among ethnically diverse early adolescents (Miconi, Moscardino, Altoè, & Salcuni, 2018). However, little is known about the factors that may enhance or buffer the effects of status-based discrimination on early adolescents’ emotional-behavioral difficulties, especially in the context of Chinese rural-to-urban migration.…”
Section: Discrimination and Emotional-behavioral Problems In Migrant mentioning
confidence: 99%
“…Second, we investigated whether self-related and other-related EA moderated the expected link between perceived discrimination and emotional-behavioral problems as rated by early adolescents and teachers. In doing so, we controlled for age, gender, SES, and fluid intelligence as these variables have been shown to influence both EA and youth’s adjustment problems (Chung et al, 2019; Mancini et al, 2013; Miconi, Moscardino et al, 2018; Shelton & Harold, 2008). Given the lack of studies on the moderating role of EA (self/other) in the status-based discrimination-socioemotional adjustment link, no specific hypotheses were generated in this regard.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the importance of parenting and its changes is highlighted by its evident impact on the stability of emotionalbehavioral problems in children (Alayi, 2013;Chen et al, 2017;Cimino et al, 2018;Diaz, 2005;Gau & Chang, 2013;Mejia et al, 2012;Miconi et al, 2018;Wolfe & McIsaac, 2011;Zuckerman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%